Development of sustainable healthcare financial managemetn framework for medical centers in Region I Philippines - Tagudin, Ronalyn R. (Divine Word College of Laoag : [s.n.], 2021)
The study focused on the Medical Centers compliance to Public Financial Management (PFM) along budget formulation, budget legislation, budget execution, and budget accountability, challenges in implementing (PFM) along health financing function in terms of raising revenue and sub- allotment of funds, and misalignment between public financial management and health financing function in terms of low budget allocations, and underspending to achieve the shared goals in sustainable healthcare financial management along financial accountability, sufficient financing, and equitable and efficient use of resources. These served as the bases in the formulation of the Sustainable Healthcare Financial Management Framework for Medical Centers in Region I. The study utilized the Research and Development (R&D) method using survey questionnaire to gather data. Involved in the study were six respondents composed of Financial and Management Officer II and Budget Officers of the Medical Centers in Region 1, and seven experts as validators. Frequency, percentage, arithmetic, mean and weighted mean were used to analyze and interpret the data.
Bibliography: pages 326-333.
CHED-La Union
Keywords: Financial management; Medical centers -- Region 1.